Avaliação da aplicação da torta de Attalea speciosa (Babaçu) como biosorvente na remoção de cobre e zinco presentes em água residuária proveniente da atividade de suinocultura - Caixeta, Laís Ferreira (2023)
Pig farming is an old process that moves the economy of the whole country, however the practice uses a large volume of water in several stages. In view of this, exorbitant loads of wastewater containing copper (Cu) and zinc (Zn), heavy metals, are generated. Since water courses receive several releases of waste, which are sometimes even clandestine, it becomes extremely important that all effluent released fits the values stipulated by CONAMA Resolution No. 430 of May 13, 2011. For this to happen, the use of the biosorption process is the most suitable for removing heavy metals, as it is economically viable and contributes to the use of vegetable masses considered waste. Therefore, this work aims to evaluate the potential of Attalea speciosa (Babassu) piece as a biosorbent in the treatment of wastewater with Cu and Zn, where tests were carried out with the natural and thermally modified material. Thus, analyzes of twelve physical-chemical and microbiological parameters will be carried out before and after the biosorption process, comparing them to the maximum values established in table two of CONAMA Resolution No. 430 of May 13, 2011. The results to be obtained will contribute to to the treatment of water and effluents, being able to serve localities, directly influencing the environmental quality of the most diverse biomes. Among the results, the dose of 37.5 g/L behaved excellently in the present work because it presented the best removal rates, and activated adsorbent carbon proved to be the most efficient among the desired adsorbents for the treatment of effluents from pig farming due to its decontaminating characteristics. The results obtained contribute to the treatment of water and effluents, being able to serve localities, directly influencing the environmental quality of the most diverse biomes.